Mitigating moisture stress in bhendi through osmolyte application - Amutha, R; Parameswari , C; Gowthami, R; Kavitha, M P; Sudhakar, G; Geetharani , P; Madhan Mohan, M; Nithila, S; Aananthi, N (Plant Science Today, 2024)
The purpose of this study was to identify the best osmolyte for foliar application to overcome moisture stress under field conditions in Bhendi (Abelmoschus esculentus L. Moench). Foliar applications of the osmolytes, viz., proline (50 mM), glycine betaine (50 mM), ascorbic acid (100 ppm), salicylic acid (100 ppm) and KCl (1 %) were applied twice, at 25 and 45 days after sowing (DAS), to mitigate moisture stress imposed by withholding irrigation during the vegetative and reproductive phases of crop growth. Data on yield parameters and yield were recorded. The results revealed that, in terms of the yield attributes, foliar sprays of proline (50 mM) resulted in increased pod length (12.2 cm) and higher pod yield per plant (335.1 g) in Bhendi. However, the highest benefit cost ratio of 1.52 and 1.23 was obtained by applying KCl (1%) followed by salicylic acid (100 ppm) during moisture stress at the reproductive stage. From the study, it is concluded that foliar sprays of proline (50 mM) and salicylic acid (100 ppm) were effective in mitigating moisture stress under field conditions in Bhendi.